2019
DOI: 10.1016/j.ebiom.2019.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Integrative proteogenomic analyses of human tumours identifies ADNP as a novel oncogenic mediator of cell cycle progression in high-grade serous ovarian cancer with poor prognosis

Abstract: BackgroundDespite toxic side effects and limited durable response, the current standard-of-care treatment for high grade serous ovarian cancer (HGSOC) remains platinum/taxane-based chemotherapy. Given that the overall prognosis has not improved drastically over the past several decades, there is a critical need to understand the underlying mechanisms that lead to tumour development and progression.MethodsWe utilized an integrative proteogenomic analysis of HGSOC tumours applying a poor prognosis gene expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 54 publications
(104 reference statements)
2
23
0
Order By: Relevance
“…Our study shows that ADNP activated the AKT-MDM2-p53 signaling pathway, mediated the degradation of p21 and the stability of cyclin D1, and promoted the proliferation of tumor cells. Consistent with our research, a number of studies have reported that ADNP plays an important role in regulating cell growth, proliferation in some types of sarcomas and neuronal tissue as well as modulating AKT signaling pathway ( 25 ). AKT signaling also plays an important role in CD8 + T cell differentiation and regulatory T cell survival ( 37 39 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study shows that ADNP activated the AKT-MDM2-p53 signaling pathway, mediated the degradation of p21 and the stability of cyclin D1, and promoted the proliferation of tumor cells. Consistent with our research, a number of studies have reported that ADNP plays an important role in regulating cell growth, proliferation in some types of sarcomas and neuronal tissue as well as modulating AKT signaling pathway ( 25 ). AKT signaling also plays an important role in CD8 + T cell differentiation and regulatory T cell survival ( 37 39 ).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we found that the mRNA and protein expression of ADNP were upregulated compared with normal bladder urothelial tissues, and overexpression of ADNP protein was significantly associated with higher pathological grade, advanced clinical stage, and poor prognosis in BC patients. Consistent with our observations, DNA amplification and overexpression of the transcription factor ADNP were identified in high-grade and poorly prognostic ovarian cancer (25).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, emerging evidence also suggests that dysregulation of cell cycle signaling cross-cascade is commonly been observed in a broad range of human cancers [ 34 , 35 ]. Especially, relevant co-DEGs were also most striking in cell cycle pathway associated highly with the tumorigenesis and progression of ovary cancer [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of EBioMedicine, Gatza and colleagues show through an integrative proteogenomic analysis of publicly available datasets that amplification and overexpression of ADNP (Activity Dependent Neuroprotector Homeobox) are associated with poor prognosis in high-grade serous carcinoma (HGSC), and further demonstrate its oncogenic potential via in vitro studies [1].…”
mentioning
confidence: 99%